Science and Engineering Students: are they entrepreneurial? - Lope Pihie, Zaidatol Akmaliah; Abdullah Sani, Abdullah Salleh (Common Ground Publishing, 2008)
A study was conducted to determine entrepreneurial intention of science and engineering students in Malaysian education system. Data were collected via questionnaire. Sample of the study comprised of seven hundred and fifteen students from normal secondary schools and technical secondary schools. The instrument has a high reliability values. Findings indicate that the students’entrepreneurial intention is in the moderate to low category. They perceived that they have moderate support to be an entrepreneur and their attitude towards self-employment is moderate. This study suggests that science and engineering students need to be exposed to business management and entrepreneurial competencies so as to increase their entrepreneurial intention and efficacy.